Enhancing the functionality of cross-linked chitosan coating on vibration damaged Nanguo pears. (1st June 2022) - Yan, Xirui; Dong, Tungalag; Yun, Xueyan; Liu, Bo; Meng, Jie
Abstract: To improve the film-forming ability and gas permeability of chitosan (CS), cross-linked CS was prepared via cross-linking reaction with diepoxy-poly (ethylene glycol) (PEG) and used for coating preservation of vibration damaged Nanguo pears. Results showed that the elongations at break of cross-linked CS films increased from 10.4 to 31.5 cm/100 cm with PEG insertion. Meanwhile, the carbon dioxide/oxygen (CO2 /O2 ) perm-selective ratio increased from 3.48 to 6.02 with 37.5 g/100 mL PEG addition, which is beneficial for the formation of a low O2 and high CO2 microenvironment. Both disc diffusion assay and in vivo antimicrobial activity assay on pears revealed that the CS-PEG coating can effectively inhibit the growth of spoilage organisms. CS-PEG coated pears also have lower respiration rates and malondialdehyde content. Principal component analysis displayed that CS-PEG coating has a significant effect on hardness and sensory quality of pears. The CS-PEG coated vibration damaged pears maintained a better physical appearance and remarkable hardness for 25 days. Graphical abstract: Image 1 Highlights: Cross-linked CS-PEG films were prepared via the epoxy-amine and crosslinking reaction. . The elongation at break of Cross-linked CS film was increased by triple with PEG. . CO2 /O2 perm-selective ratio of CS-PEG films increased from 3.48 to 6.02 . CS-PEG film had better antimicrobial activity than CS. . CS-PEG coated vibration damaged pears maintain better quality by 25th day. .